Purification and certain properties of a bacteriocin from Streptococcus mutans. - Ikeda, T (1982)
An inhibition factor from Streptococcus mutans strain C3603 (serotype c) was purified and isolated, and its properties indicated that it was a bacteriocin. Bacteriocin C3603 is a basic protein with a pI value of 10 and a molecular weight of 4,800. The activity of this bacteriocin was not affected by pH over a range of 1.0 to 12.0 or by storage at 100 degrees C for 10 min at pH 2.0 to 7.0 or storage at 121 degrees C for 15 min at pH 4.0. Pronase; papain, phospholipase C, trypsin, and alpha-amylase had no effect on the activity of the bacteriocin, whereas alpha-chymotrypsin and pancreatin were partially active against it. Bacteriocin activity was greater against certain S. mutans strains of serotypes b, c, e, and f than against certain S. mutans strains of serotypes a, d, and g. Bacteriocin C3603 was also effective against selected strains of S. sanguis, S. salivarius, S. bovis, S. faecium, S. lactis, Lactobacillus casei, L. plantarum, L. fermentum, Bifidobacterium bifidum, Bifidobacterium longum, Propionibacterium acnes, and Bacteroides melaninogenicus, but it was not effective against certain strains of Escherichia coli, Klebsiella pneumoniae, Corynebacterium parvum, and Candida albicans. The inhibition of S. mutans strains BHT and PS-14 by bacteriocin C3603 was found to be due to the bacteriocidal activity of the bacteriocin. When water or a diet containing bacteriocin C3603 was consumed by gnotobiotic and specific pathogen-free rats infected with S. mutans PS-14, the caries score was found to be significantly reduced.